2019
DOI: 10.1021/acs.langmuir.9b01730
|View full text |Cite
|
Sign up to set email alerts
|

Adhesive Properties of Adsorbed Layers of Two Recombinant Mussel Foot Proteins with Different Levels of DOPA and Tyrosine

Abstract: Using a surface forces apparatus and an atomic force microscope, we characterized the adhesive properties of adsorbed layers of two recombinant variants of Perna viridis foot protein 5 (PVFP-5), the main surface-binding protein in the adhesive plaque of the Asian green mussel. In one variant, all tyrosine residues were modified into 3,4-dihydroxy-Lphenylalanine (DOPA) during expression using a residuespecific incorporation strategy. DOPA is a key molecular moiety underlying underwater mussel adhesion. In the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 49 publications
3
37
2
Order By: Relevance
“…Adhesion is thus attributed due to the progressive stretching of flexible polymer‐like segments in a random network of proteins, eventually leading to protein bond rupture. [ 14,15 ] The network is both cross‐linked (e.g., via cation–π bonds or amyloidogenic interactions inducing β‐sheet formation) and attached to the Si 3 N 4 probe and TiO 2 substrate (e.g., Dopa–surface bonds). Adhesive peaks were due to the rupture of protein bonds, either a protein–protein cross‐link or protein–surface bond.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Adhesion is thus attributed due to the progressive stretching of flexible polymer‐like segments in a random network of proteins, eventually leading to protein bond rupture. [ 14,15 ] The network is both cross‐linked (e.g., via cation–π bonds or amyloidogenic interactions inducing β‐sheet formation) and attached to the Si 3 N 4 probe and TiO 2 substrate (e.g., Dopa–surface bonds). Adhesive peaks were due to the rupture of protein bonds, either a protein–protein cross‐link or protein–surface bond.…”
Section: Resultsmentioning
confidence: 99%
“…Adhesive peaks were due to the rupture of protein bonds, either a protein–protein cross‐link or protein–surface bond. The maximum adhesive force F 0 on the order of 0.1–1.0 nN is consistent with the rupture of single bonds, [ 11e,14 ] whereas the adhesive energy W = −∫ FdD characterizes the adhesive properties of the protein network, cumulating the effect of breaking multiple bonds of different types. Both F 0 and W showed a large variation among different measurements, even when all experimental parameters such as AFM tip velocity, or dwell time and maximum load at contact were kept constant (Figure S6c,d, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, the adhesion ability of dipeptides with Lys at the N terminus (Lys-Dopa) is stronger than C terminus (Dopa-Lys), indicating that the cooperative Lys and Dopa binding to hydrophilic surfaces strongly depends on the protein sequences (29). As for the adhesive proteins, increasing studies also showed that recombinant protein enriched with Tyr rather than Dopa has strong adhesive ability (32)(33)(34)(35). All these studies are consistent with our findings based on MD simulations and lap shear experiments.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the Dopa-based peptide containing insufficient Lys exhibits limited adhesion to hydrophilic surface (30). Moreover, increasing studies showed that the peptides containing Lys and unmodified Tyr can also adsorb to hydrophilic surfaces (31)(32)(33)(34)(35). Together, although the crucial role of Dopa to enhance the mussel attachment by promoting the protein cross-linking has been well established (36)(37)(38), its effect on adhesive interaction is under debate.…”
Section: Introductionmentioning
confidence: 99%